Improved PCR-RFLP Method For Her-2 Ile655val Breast Cancer Patients Detection - Desriani, -; Arif Harahap, Wirsma; Besari, Ariza Yandwiputra (International Journal on Advanced Science, Engineering and Information Technology, 2016)
HER2 is a protein that is essential to the process of differentiation, proliferation, tissue development and other physiological processes. HER-2 overexpression was occurred in 20-30% of breast cancer patients. Targeted therapies was performed using trastuzumab, on the basis of the examination by immunohistochemistry. Single nucleotide polimorphisme (SNP) Ile655Val were found on HER-2, which indicates the risk of cancer as well as a predictive factor of treatment with targeted therapies. The method had been used for HER-2 SNP detection is using TaqMan method which is expensive, or PCR RFLP which is cheaper and easier. 148bp PCR product was widely used in PCR RFLP for HER-2 Ile655Val SNP detection confirmed at high concentration of agarose (3%). This study conducted to improve the PCR RFLP methods become more economical and more efficient by increasing the size of the PCR products confirmed with low concentration of agarose which have lower prices. The results showed that PCR RFLP method developed in this study, 480bp PCR product restricted with BsmAI confirmed with 2% agarose, has been successfully performed with more economist and a high level of reproducibility.